Clinical and magnetic resonance imaging predictors of disease progression in multiple sclerosis: a nine-year follow-up study. (February 2014) - Lavorgna, L; Bonavita, S; Ippolito, D; Lanzillo, R; Salemi, G; Patti, F; Valentino, P; Coniglio, G; Buccafusca, M; Paolicelli, D; d'Ambrosio, A; Bresciamorra, V; et al.
Objective: The objective of this paper is to identify clinical or magnetic resonance imaging (MRI) predictors of long-term clinical progression in a large cohort of multiple sclerosis (MS) patients. Methods: A total of 241 relapsing–remitting (RR) MS patients were included in a nine-year follow-up (FU) study. The reference MRIs were acquired at baseline (BL) as part of a multicenter, cross-sectional, clinical-MRI study. Volumetric MRI metrics were measured by a fully automated, operator-independent, multi-parametric segmentation method. Clinical progression was evaluated as defined by: conversion from RR to secondary progressive (SP) disease course; progression of Expanded Disability Status Scale (EDSS); achievement and time to reach EDSS 4. Results: We concluded that conversion from RR to SP (OR 0.79; CI 0.7–0.9), progression of EDSS (OR 0.85; CI 0.77–0.93), achievement of EDSS 4 (OR 0.8; CI 0.7–0.9), and time to reach EDSS 4 (HR 0.88; CI 0.82–0.94) were all predicted by BL gray matter (GM) volume and, except for progression of EDSS, by BL EDSS (respectively: (OR 2.88; CI 1.9–4.36), (OR 2.7; CI 1.7–4.2), (HR 3.86; CI 1.94–7.70)). Conclusions: BL GM volume and EDSS are the best long-term predictors of disease progression in RRMS patients with a relatively long and mild disease.